A multilevel study of the dual effects of leader political skill on follower performance - Beenish Qamar (Taylor & Francis Group, 2019)
Using a sample of 61 teams (i.e., 305 employees and 61 leaders) from multiple banks, this study examines a multilevel model of the influence of dual effects of leader political skill (LPS) on followers’ performance at two levels. We examined the effect of followers’ perception of individual-focused LPS on followers’ individual performance rated by their leaders and the effect of followers’ perception of group-focused LPS on leader-rated team performance. In addition, we also examined a cross-level effect from group-focused LPS at team level to follower performance at individual level. The results revealed that individual-focused LPS predicts followers’ performance at the individual level and the group-focused LPS predicts team performance at the team level. Results also supported the cross-level effect from group-focused LPS at team level to followers’ performance at individual level. Strengths, limitations, and implications for both theory and practice as well as for future research are also discussed.